Pakistan’s Crisis Management: Examining Proactive and Reactive Strategies - Mubeen Adnan (Journal of Political Studies, 2014)
Pakistan is a unique case by itself, which is facing number of crises at a time. Pakistan has witnessed many disasters and crises in recent years like earthquakes in 2005 and 2013, floods in 2007, 2010, 2011 and in 2012, energy crisis and security crisis from internal and external sources etc. These earthquakes and devastating floods threaten the lives of millions and created the crisis of displacement of people within Pakistan. Government of Pakistan has responded to these by committing effort and resources to crisis prevention and recovery initiatives. Government has made Earthquake Rehabilitation and Reconstruction Authority (ERRA), National Disaster Management Authority (NDMA), National Institute for Disaster Management (NIDM) and Planning Commission. Provincial Disaster Management Authority (PDMA), it operates under the provincial Disaster Management Commission. Another District Disaster Management Unit (DDMU) was made to coordinate or implement the policies to grass root level of each province. This research would focus on Pakistan’s disaster (earthquakes and floods) management and to explore the opportunities for growth. Amazingly, government of Pakistan still struggling to put plans in place in anticipation of a catastrophe. Disaster handling plans did not meet the requirements when timing and initial response matter as much, the institutions which are made for the management did not work and did not carry out their responsibility. These disasters led a situation of crisis again and again in Pakistan. History of Pakistan shows that the government is not effectively integrating crisis management into policy making and planning. Government of Pakistan claim that it has made proactive strategies to cope with crisis situation but practically these strategies are not working when need to work. To confront the crises effectively, it is essential to strengthen the civilian government’s capacity to plan for and to cope with crises.